TRANSFORMATIONAL PROCESSES IN THE HIGHER EDUCATION SYSTEM OF UZBEKISTAN: ACHIEVEMENTS AND PROBLEMS - Сиддиқов Р. Б. (TARIXIY TADQIQOTLAR, 2025)
The article analyzes the transformational processes that took place in the higher education system of Uzbekistan as a result of the implementation of the National Training Program. It also reflects the structural changes and new approaches to the training of highly qualified personnel that have occurred in the higher education system. The problems that have arisen in the training of national personnel and financing of higher education, and their causes, are indicated.